ETIKA DALAM BERSOSIAL DALAM PANDANGAN PANCASILA DAN ISLAM - Muhamad Azrahul Shidik (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2026)
ABSTRACT Social ethics is a fundamental aspect of human life that regulates how individuals relate to each other within a society. In the Indonesian context, two primary value systems serve as the normative foundation for social life: Pancasila as the national ideology and Islam as the religion of the majority population. Pancasila, through its five principles, offers a comprehensive ethical framework encompassing divinity, humanity, unity, deliberation, and social justice. Islam, through the teachings of the al-Qur'an and the Hadith of the Prophet Muhammad, provides a rich system of social ethics centered on noble character (akhlak), brotherhood (ukhuwwah), cooperation (ta'awun), justice (al-'adl), and universal compassion. This study examines the concept of social ethics from the perspectives of both Pancasila and Islam and analyzes the points of convergence between the two systems. Using a qualitative approach with library research methods and content analysis techniques, this study finds that Pancasila and Islamic social ethics share deeply aligned core values, including upholding human dignity, promoting justice and social solidarity, valuing tolerance and pluralism, and emphasizing the importance of deliberation in communal decision-making. The integration of Pancasila and Islamic values in social ethics is not only theoretically possible but also practically necessary to build a harmonious, just, and civilized Indonesian society in the face of contemporary social challenges. The findings of this study are expected to contribute to the development of social ethics education rooted in the nation's cultural and religious values. Keywords: social ethics, Pancasila, Islam, Al-Qur'an, social values